Non‐invasive urine markers for the differentiation between RCCs and oncocytoma. Issue 5 (7th May 2021) - von Brandenstein, Melanie; Herden, Jan; Köditz, Barbara; Huerta, Manuel; Nestler, Tim; Heidenreich, Axel; Fries, Jochen W.U.
Abstract: Background: Recently, our group showed that Vim3 is overexpressed in tissue samples of renal oncocytomas and Mxi‐2 in clear cell renal carcinoma (ccRCC). The mechanism leading to the truncation of both proteins is known and involves with two miRs, both detectable in urine. Since the analysis of miRs is time‐consuming, our aim was to identify the truncated proteins in urine instead. Furthermore, urine samples from small renal masses (SRMs) (n = 45, <4 cm) were analyzed to get a pre‐surgical differentiation of the cancer subtypes. Methods: Urines were accessed from the urological biobank (n = 350). Proteins were isolated from urine samples, and Western blots were performed. Each sample was analyzed with ELISA for the expression of Vim3 and Mxi‐2. A lateral flow assay was established. For the detection of SRMs, the miRs were isolated and qRT‐PCR was performed. Results: A significant increase of Vim3 in urines from patients with oncocytoma (n = 20) was detectable with ELISA compared to all other subtypes of RCCs (chromophobe (n = 50), papillary (n = 40), ccRCC (n = 200), and controls (n = 40) (***p < 0.0001)). Mxi‐2 was predominantly overexpressed in ccRCCs (***p < 0.0001). Lateral flow assay of Vim3 and Mxi‐2 shows two bands in the case of oncocytoma and ccRCC indicating the specificity of this test. For SRMs, an overexpression of miR‐15a/Mxi2 was detectable in urine samples from ccRCC and chromoRCC patients. In contrast to that, miR‐498/Vim3 were predominantly overexpressed in oncocytoma patients. Conclusion: Both proteins (Vim3 and Mxi‐2) were detectable in patients' urines and can be used for the non‐invasive differentiation of kidney cancers. Abstract : In urine sample from clear cell renal carcinoma (RCC) and oncocytoma patients, two miRs (miR‐15a and miR‐498) were significantly overexpressed. This overexpression of the miRs leads to the production of two truncated proteins (Mxi‐2 and Vim3), both detectable in urine samples. We analyzed n = 350 urine samples from healthy patients and those with different urological tumors. The noticed overexpression of Mxi‐2 and Vim3 in urine samples significantly correlates with the tumor entity. Overexpression of Mxi‐2 in RCC samples and Vim3 in oncocytomas, also in small renal cancers (<4 cm), is possible even before surgery.